Peer workers and the participation of socially marginalized individuals and groups - Llobet Estany, Marta; Baillergeau, Evelyne; Thirot, Myriam (Cuadernos de Trabajo Social, 2012)
This paper presents some results of a research project named Proximité et citoyenneté en milieu urbain. Les leçons dela pratique au Québec, aux Pays-Bas et en Espagne undertaken with the support of the French Government’s Citoyennetéurbaine (PUCA) Program.The aim of this exploratory project is to analyze outreach practices that seek to promote participation of people in verydifficult social and economic situations. Proximity and participation are the two main axes of these practices. The researchwas carried out in Amsterdam, Montreal and Barcelona, and here we present the results for the two latter cities.The focus here is on the primary results that have to do with «existential proximity», i.e., social interventions carriedout by people in similar situations to the target population. Peer workers or pairs aidants have a key role in reaching outto people with little contact with services and institutions, and have a decisive role in enabling the participation of marginalizedgroups. We identify some key elements of such practices, based on interviews with practitioners, peer workersand third sector and public service users.
Keywords: social intervention; proximity; peer worker; participation; social exclusion